Screening for Tuberculosis With Xpert MTB/RIF Assay Versus Fluorescent Microscopy Among Adults Newly Diagnosed With Human Immunodeficiency Virus in Rural Malawi: A Cluster Randomized Trial (Chepetsa). (27th July 2018) - Ngwira, Lucky G; Corbett, Elizabeth L; Khundi, McEwen; Barnes, Grace L; Nkhoma, Austin; Murowa, Michael; Cohn, Silvia; Moulton, Lawrence H; Chaisson, Richard E; Dowdy, David W
Abstract: Background: Tuberculosis (TB) remains the leading cause of death among human immunodeficiency virus (HIV)–infected individuals globally. Screening for TB at the point of HIV diagnosis with a high-sensitivity assay presents an opportunity to reduce mortality. Methods: We performed a cluster randomized trial of TB screening among adults newly diagnosed with HIV in 12 primary health clinics in rural Thyolo, Malawi. Clinics were allocated in a 1:1 ratio to perform either point-of-care Xpert MTB/RIF assay (Xpert) or point-of-care light-emitting diode fluorescence microscopy (LED-FM) for individuals screening positive for TB symptoms. Asymptomatic participants were offered isoniazid preventive therapy in both arms. Investigators, but not clinic staff or participants, were masked to allocation. Our primary outcome was the incidence rate ratio (RR) of all-cause mortality within 12 months of HIV diagnosis. Results: Prevalent TB was diagnosed in 24 of 1001 (2.4%) individuals enrolled in clinics randomized to Xpert, compared with 10 of 841 (1.2%) in clinics randomized to LED-FM. All-cause mortality was 22% lower in the Xpert arm than in the LED-FM arm (6.7 vs 8.6 per 100 person-years; RR, 0.78 [95% confidence interval CI, .58–1.06]). A planned subgroup analysis suggested that participants with more advanced HIV (World Health Organization clinical stage 3 or 4) disease had lower mortality in clinics randomized to Xpert than to LED-FM (RR, 0.43 [95% CI, .22–.87]). Conclusions: In rural Malawi, using point-of-care Xpert MTB/RIF to test symptomatic patients for TB at the time of HIV diagnosis reduced all-cause 12-month mortality among individuals with advanced HIV. Clinical Trials Registration: NCT01450085. Abstract : In this randomized trial of screening for tuberculosis among adults in rural Malawi with newly diagnosed HIV, all-cause mortality was 22% lower overall, and 57% lower among participants with clinically advanced HIV, when using point-of-care Xpert MTB/RIF vs point-of-care fluorescence microscopy.